The Effect Of Internet Use Habit Toward English Achievement: Survey Study In Smp Al Azhar 8 Bekasi - Syaf, Okfida Yani (Syntax Literate, 2020)
Students nowadays interact more frequently through the internet using English. As an international language, English is used by most internet users, both by application companies and social networks, as well as by users. Internet usage can be more easily obtained, especially in big cities. This affects the students’ way of thinking, learning and behaving because they can learn everything easily and quickly through online media available at the internet. The aim of this research is to show the effect of internet use habit on English achievement for class VIII students at SMPI Al Azhar 8 in Bekasi. This research based on survey methods using technical correlational analysis. While the data and information were obtained by a questionnaire. The sample is taken with purposive sampling technique that is 44 students. Based on the results of the study, it can be concluded that: There is a significant effect of the habit of interacting through the internet on the English achievement. This is evidenced by the acquisition of the results of the Sig. 0,000 <0,05dan t value = 4,365 which means there is a significant effect.